Feminist rhetorical resilience - Flynn, Elizabeth A., editor; Sotirin, Patricia, editor; Brady, Ann, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2012)
Although it is well known in other fields, the concept of "resilience" has not been addressed explicitly by feminist rhetoricians. This collection develops it in readings of rhetorical situations across a range of social contexts and national cultures. Contributors demonstrate that resilience offers an important new conceptual frame for feminist rhetoric, with emphasis on agency, change, and hope in the daily lives of individuals or groups of individuals disempowered by social or material forces. Collectively, these chapters create a robust conception of resilience as a complex rhetorical process, redeeming it from its popular association with individual heroism through an important focus on relationality, community, and an ethics of connection. Resilience, in this volume, is a specifically rhetorical response to complicated forces in individual lives. Through it, Feminist Rhetorical Resilience widens the interpretive space within which rhetoricians can work.
Introduction: Feminist Rhetorical Resilience-Possibilities and Impossibilities / Elizabeth A. Flynn, Patricia Sotirin, and Ann Brady -- 1. Vandana Shiva and the Rhetorics of Biodiversity: Engaging Difference and Transnational Feminist Solidarities in a Globalized World / Eileen E. Schell -- Response On the Politics of Writing Transnational Rhetoric: Possibilities and Pitfalls / Arabella Lyon and Banu Özel -- Reflection / Eileen E. Schell -- 2. The Traveling Fado / Kate Vieira -- Response Traveling Literacies / Janet Carey Eldred -- Reflection / Kate Vieira -- 3. Virginity and Hymen Reconstructions: Rural, Migrant Women as Agents of Literate Practices in Turkey / Iklim Goksel -- Response Problematizing Literacy / Elizabeth Chiseri-Strater -- Reflection / Iklim Goksel -- 4. Diversity and the Flexible Subject in the Language of Spousal/Partner Hiring Policies / Amy Koerber -- Response Expanding the Sites of Struggle over the "Flexible Subject" in Academe / Shirley K Rose -- Reflection / Amy Koerber -- 5. A Case Study in Resilience: Fabricating a Feminine Self in a Man-Made Era / Frances J. Ranney -- Response Philanthropy as Interpretation, Not Charity: Jane Addams's Civic Housekeeping as Another Response to the Progressive Era / Kate Ronald -- Reflection / Frances J. Ranney -- 6. From "Mothers of the Nation" to "Mothers of the Race": Nineteenth-Century Feminists and Eugenic Rhetoric / Wendy Hayden -- Response Strategic Collusion in the History of American Women Rhetors / Nan Johnson -- Reflection / Wendy Hayden -- 7. No One Wants to Go There: Resilience, Denial, and Possibilities for Queering the Writing Classroom / Jennifer DiGrazia and Lauren Rosenberg -- Response On Impossibility / Jacqueline Rhodes and Jonathan Alexander -- Reflection / Jennifer DiGrazia and Lauren Rosenberg.
Keywords: Feminist theory; Rhetoric -- Social aspects; Resilience (Personality trait); Women -- Communication